Clinical and serological correlates of antinucleosome antibodies in South Africans with systemic lupus erythematosus - Tikly, M.; Gould, T.; Wadee, A. A.; van der Westhuizen, E.; Mokgethwa, B. B. N. (Clinical rheumatology, 2007)
Antinucleosome antibodies (AnuA) are increasingly recognized as an important biomarker in the diagnosis and subset stratification of patients with systemic lupus erythematosus (SLE). The aim of the study was to determine the sensitivity, specificity, and clinico-serological correlates of AnuA in black South Africans with SLE. We performed a cross-sectional study of 86 SLE patients attending a tertiary center and 87 control subjects. AnuA were tested using a second-generation enzyme-linked immunosorbent assay (ELISA). The sensitivity, specificity, positive predictive value, and negative predictive value of AnuA were 45.3, 94.3, 88.6, and 63.6%, respectively. The presence of AnuA were strongly associated with the co-presence of anti-dsDNA antibodies (OR = 3.4, p < 0.0005) and antihistone antibodies (OR = 15.7, p < 0.00001). Patients who were seropositive for AnuA were more likely to have skin involvement (discoid lupus and/or malar rash) and had higher SLE disease activity index (SLEDAI) scores and Systemic Lupus International Collaborative Clinics/American College of Rheumatology (SLICC/ACR) damage scores (p < 0.05). IgG anticardiolipin antibody (aCL) levels showed a significant correlation with AnuA ratios (p < 0.01). Our findings provide further evidence that AnuA are a sensitive and specific diagnostic biomarker in SLE. Moreover, our finding that the presence of AnuA, but not anti-dsDNA antibodies, are associated with worse SLICC/ACR damage scores suggest that AnuA may have a role in predicting disease outcome. The correlation between IgG aCL and AnuA is a novel finding that merits further studies to determine possible common peptide specificities of the antibodies.